IMPACT OF THE DIGITAL COMPETITIVENESS ON ECONOMIC GROWTH: EVIDENCE FROM GLOBAL ECONOMY (World Economics and Finance Bulletin, 2022)
Digital technologies are crucial components of the coming industrial revolution and have an influence on all socioeconomic endeavors in both developed and developing nations. In order to define, conceptualize, and analyze this phenomena, this study will evaluate the relevant literature on digital competition. Similar to the industrial revolution of the 19th century, which saw the development of steam power, the internal combustion engine, and the digital economy, the digital economy revolution is having a significant influence on society.Without a question, only those nations that can create a conducive atmosphere for the growth of the digital economy will be able to lead the global market.This paper proposes an analytical framework that can be used by researchers for analyzing same cases. Two main approaches are used within research, these are known as deductive and inductive approaches, and the relevant data derived from the European Commission, UNCTAD, OECD, APEC, World Bank Group and European Investment Bank were among the data providers in the latter category
Keywords: Global economy; Digitalization; Competitiveness; Digital economy